Effect of method of planting and harvesting time on growth, yield and quality of turmeric (Curcuma longa L.) - B S Gill, Balwinder Kumar (Journal of Spices and Aromatic Crops, 2009)
An experiment was conducted at Ludhiana (Punjab) to study the influence of method ofplanting (flat and ridge planting) and harvesting time (10 November-12 March) on growth,yield and of quality turmeric (Curcuma longa). Planting methods did not influence growth,yield and quality of turmeric significantly. Harvesting on 12th March produced maximumfresh rhizome yield of 28.94 t ha-1 (mean yield) of turmeric which was statistically on parwith 20th February (27.61 t ha-1) and 30th January (26.78 t ha-1) harvesting, but was significantlybetter than all the earlier harvesting dates. A similar trend was observed in processed turmericyield. The number and weight of rhizomes improved significantly with delay in harvesting.The oil and curcumin content also increased with delay in harvesting.